2020
DOI: 10.1186/s40729-020-00262-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of occlusal loading on peri-implant inflammatory cytokines in crevicular fluid: a prospective longitudinal study

Abstract: Objective The objective of the study was to evaluate the relation between occlusal loading and peri-implant crevicular fluid cytokine expression in patients with implant-supported complete fixed prostheses in both arches. Material and methods A prospective longitudinal clinical study was performed at a university clinic. Fifteen patients were selected and 11 were included. All patients had bimaxillary implant-supported complete fixed ceramo-metallic prostheses loaded at least 12 months before the beginning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Previous research has also noticed that occlusal stress triggers increases in the proinflammatory cytokines IL-1β, IL-6 and IL-17. In addition, another study showed that implants with a higher occlusal load presented higher levels of IL-10 in peri-implant crevicular fluid, which indicated the role of IL-10 in monitoring the occlusal force and counterbalancing the increased proinflammatory cytokines [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also noticed that occlusal stress triggers increases in the proinflammatory cytokines IL-1β, IL-6 and IL-17. In addition, another study showed that implants with a higher occlusal load presented higher levels of IL-10 in peri-implant crevicular fluid, which indicated the role of IL-10 in monitoring the occlusal force and counterbalancing the increased proinflammatory cytokines [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…But once again, the lack of a high degree of evidence studies is not to say that occlusal loads do not influence MBL and/or PI onset and progression. Within a still undefined “ideal threshold” (probably variable in each individual), occlusal forces transmitted to the bone may enhance both osteointegration and the features of the bone in close contact with the implant [ 108 , 109 ]. Probably, in absence of a clear definition of what exactly is “excessive occlusal load” [ 109 ] and given the complexity of exactly measuring in vivo the real strength and direction of occlusal loads in every single implant, it is difficult to clarify this point by now.…”
Section: Reviewmentioning
confidence: 99%
“…Within a still undefined “ideal threshold” (probably variable in each individual), occlusal forces transmitted to the bone may enhance both osteointegration and the features of the bone in close contact with the implant [ 108 , 109 ]. Probably, in absence of a clear definition of what exactly is “excessive occlusal load” [ 109 ] and given the complexity of exactly measuring in vivo the real strength and direction of occlusal loads in every single implant, it is difficult to clarify this point by now. Nevertheless, the loads transmitted through the implant-bone contact have lastly an influence on the RANKL/RANK/OPG pathway through the so-called “mechano-transduction phenomena” [ 108 ].…”
Section: Reviewmentioning
confidence: 99%
“…Dicho principio no parece poder establecerse en estos casos, ya que la mandíbula no se comporta igual que los huesos largos, ni las cargas que se producen en la cavidad oral son cargas estáticas. Otros trabajos mencionan que solo existe pérdida de hueso peri-implantario cuando existe una sobrecarga oclusal coexistiendo junto a inflamación de los tejidos peri-implantarios (58)(59) (60). Miyata remarca que la sobrecarga por sí sola no produce reabsorción de hueso peri-implantario, sino que se necesita que haya placa bacteriana e inflamación de los tejidos adyacentes para que se produzca daño biológico.…”
Section: 4consecuencias De Sobrecargaunclassified